ANALISIS NILAI-NILAI KETELADANAN ISLAM DALAM KARAKTER TOKOH NADZIRA SHAFA DI NOVEL 172 DAYS - Marisa Marisa; Elsa Mulya Karlina (JIP: Jurnal Ilmu Pendidikan, 2025)
This study is entitled "Analysis of Islamic Exemplary Values ​​in the Character of Nadzira Shafa in the Novel 172 Days". Where this study aims to describe Islamic character values ​​that can be represented through the main character. While the problem is how these Islamic character values ​​can be represented through the main character in this novel, namely Nadzira Shafa. The method used in this study is a qualitative approach method. This refers to a research approach that produces descriptive data in the form of written data resulting from observations of an object, namely the Novel. The definition of qualitative research is research that is descriptive and analytical. Descriptive in qualitative research means describing and explaining events, phenomena and social situations being studied. Analysis means interpreting and comparing research data. Several definitions of qualitative research. And the results of this study show that there are several quotes in the Novel 172 Days reflecting that these Islamic character values ​​can be represented through its main character, namely Nadzira Shafa